2018
DOI: 10.5152/tud.2018.71205
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in the use of healthcare services among US adults with and without a cancer diagnosis

Abstract: Men increase their healthcare utilization to that of women only after they receive diagnosis of cancer. Targeted interventions to promote utilization of preventive care services by men are needed to reduce the burden of chronic illnesses including cancer among men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…Interestingly, our study also found that the peak incidence of these conditions was generally higher for male cases than female cases when compared to their corresponding control groups. One possible explanation for this pattern could be that men are more likely to only seek care from the health-care system when they experience a serious health outcome compared to women who may access care more regularly [35][36][37][38]. Alcohol-related cancer was almost doubled among women with AUD and was five times higher among men with AUD compared to their matched controls 1 year prior to index date.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, our study also found that the peak incidence of these conditions was generally higher for male cases than female cases when compared to their corresponding control groups. One possible explanation for this pattern could be that men are more likely to only seek care from the health-care system when they experience a serious health outcome compared to women who may access care more regularly [35][36][37][38]. Alcohol-related cancer was almost doubled among women with AUD and was five times higher among men with AUD compared to their matched controls 1 year prior to index date.…”
Section: Discussionmentioning
confidence: 99%
“…One important question raised by the current study is why females are significantly less likely to undergo PET at the time of diagnosis. Men are known to use health care less compared with women prior to a cancer diagnosis; however, after a diagnosis of cancer, their rate of health care use increases to equal that of women . Prior studies have found that women are less likely to undergo imaging during presentation for bladder cancer .…”
Section: Discussionmentioning
confidence: 99%
“…Men are known to use health care less compared with women prior to a cancer diagnosis; however, after a diagnosis of cancer, their rate of health care use increases to equal that of women. 24 Prior studies have found that women are less likely to undergo imaging during presentation for bladder cancer. 25 This is in contrast to a larger study that found that men were more likely to not undergo staging compared with women.…”
Section: Impact Of Pet Vs Mri Odds Ratio and 95% CLmentioning
confidence: 99%
“…In this theory, the structuring and behaviors of gender by social practices undermine the health of men and can inform decisions to seek medical attention when needed (Figure 2 , Point 4). Men, for example, are less likely than females to engage in sun‐protective options such as sunscreen or shade, visit physicians on a yearly basis, or self‐detect melanomas (Brady et al, 2000 ; Burnside et al, 2018 ; Holman et al, 2018 ). While this theory may contribute partly to sex differences in melanoma incidences, it does not necessarily account for differences in progression and survival after disease initiation (Figure 1B ).…”
mentioning
confidence: 99%